Enhancing coordination in water management through communication tools: results from experimental games in Coastal Bangladesh - Mitra, A.; Buisson, Marie-Charlotte; Bastakoti, Ram C. (Uopen Journals, 2017)
Canal siltation is a pervasive problem in coastal Bangladesh causing water-logging and losses in crop yield. Although timely maintenance of canals through regular contributions from the community can solve this problem; it often breaks down because of the free riding issue, a common feature in the provision of public goods. Previous literature on experimental games has shown how different communication strategies can help to achieve coordination. We conducted experimental games with the aims to: (i) determine the effectiveness of these communication institutions in the specific problem of maintenance of canal; and (ii) compare the relative effectiveness of different communication mechanisms. Playing these games was also a part of a participatory action research approach with the idea that community members would have a clearer understanding of the incentives and constraints of contribution for canal maintenance. The basic insight from our study is that any institution that enables more information sharing about both the intended contribution and setting the group norm translates into better coordination among the users to increase the group income towards Pareto Optimum outcomes. The lessons from these games could potentially open up a forum of discussion and help the villagers in their future communications as a tool for understanding and testing different alternatives for community management of natural resources. The results are also of interest for development practitioners supporting community organizations for sustaining local public goods.